Heterostructured Co3O4/VO2 nanosheet array catalysts on carbon cloth for hydrogen evolution reaction. (22nd May 2022) - Hu, Mingwei; Hu, Jinrong; Zheng, Yingqiu; Zhang, Song; Li, Qizhong; Yang, Meijun; Goto, Takashi; Tu, Rong
Abstract: Developing highly efficient, low-cost, and robust water splitting hydrogen production catalysts is critical for hydrogen energy applications. This study presents the synthesis of Co3 O4 /VO2 heterogeneous nanosheet structures on carbon cloth (Co3 O4 /VO2 /CC). The obtained Co3 O4 /VO2 /CC hybrid catalyst has a low overpotential of 108 mV at a current density of 10 mA cm −2, a Tafel slope of 98 mV dec −1, and high stability in 1.0 M KOH for 10 h. The experimental results and density functional theory (DFT) calculations results also show that Co3 O4 coupled with VO2 in Co3 O4 /VO2 /CC can optimize hydrogen adsorption energy and facilitate electron transport, thereby accelerating the catalytic kinetics for hydrogen evolution reaction (HER). This work also provided an alternative method to design and construct non-noble metal oxide-based catalysts for alkaline hydrogen production. Highlights: The Co3 O4 /VO2 /CC hybrid catalyst needs 108 mV to reach 10 mA cm −2 in 1.0 M KOH. DFT calculations confirm that the Co3 O4 /VO2 interface optimize the hydrogen adsorption energy. Co3 O4 /VO2 heterogeneous nanosheet structure provide more active site.